KEWENANGAN KOMISI KEJAKSAAN TERHADAP TUGASNYA UNTUK MELAKUKAN PENGAWASAN KHUSUSNYA KEPADA KEWENANGAN PENUNTUT UMUM - Indrawan Ariadi, Putu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
Legal writing on the authority of the commission is entitled to the prosecutor's duty to carry out supervision authority specifically to the public prosecutor. The background of the writing of this law is the increasing distrust and dissatisfaction of the public on the performance of law enforcement agencies and institutions secaara public prosecutor's office in particular. The method in this research is using normative where in the writing of this law into the background issues penelituan is going to commissions and the prosecutor in the line of duty to supervise the performance of the public prosecutor and what are the constraints commission prosecutor in supervision where the constraint is divided into two parts: internal constraints and external constraints. In the study found that in order to carry out the process of supervision of the public prosecutor, the prosecutor commission can not directly supervise, why is that? this is because there is an internal watchdog in the body prosecutor who take a stand if there is a public prosecutor alleged violation. Constraints of commission prosecutor in carrying out the control can be internal constraints such an evil do not want sightings of the prosecutor who was in trouble, while the external constraints such as obstruction by certain groups who want to impede the work of the commission prosecutor. Therefore let fungis of the prosecutor commission is enforced to match the function of other commissions in Indonesia is the role bgitu stand out and let people participate in helping carry out the task of the prosecutor's commission.
Keywords: Prosecutorial Commission; Supervision; prosecutor.